UAW VEBA - Rosenthal, Jean W., 1945-; Elias, Jaan; Goetzmann, William N.; Garska, Stanley; Thomas, Jacob (London : SAGE Publications Ltd, 2017)
Negotiations between the United Auto Workers (UAW) and General Motors (GM) in 2007 created a new entity to provide retiree healthcare, a Voluntary Employee Beneficiary Association (VEBA). The agreement shifted the responsibility and the risk for retiree healthcare to the new VEBA trust. GM would provide a set amount of money for retiree health coverage and would no longer guarantee "defined benefits," promises of specific retiree healthcare benefits, which the UAW had negotiated with GM over many years. After settling with GM, the UAW negotiated similar agreements with Ford and Chrysler.
Originally published in Rosenthal, J. W., Elias, J., Goetzmann, W. N., Garska, S., & Thomas, J. (2008). UAW VEBA. 08-035. New Haven, CT: Yale School of Management, Yale University. Retrieved from: https://vol09.cases.som.yale.edu/uaw-veba.
Description based on XML content.
Keywords: elektronické knihy; electronic books; International Union, United Automobile Workers of America (CIO); Voluntary Employee Beneficiary Association; Compensation management; Medical care; Automobile industry and trade; Automobile industry workers